TRADISI MAROSOK DALAM TRANSAKSI JUAL BELI TERNAK DI PASAR TERNAK KOTA PAYAKUMBUH, SUMATERA BARAT - ", Regina; Marnelly, T.Romi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Marosok tradition is one uniqe traditions of West Sumatera, where thistradition is implemented in the system of sale and purchase transaction oflivestock. Marosok in Indonesian is to feel, and hold something without seeingwhat the stuff bit only feel it based on brain and feeling. This tradition beginswhen the buyer has found the cattle that are considered suitable, than there willbe bargaining price of levestock. And bargaining is done by way of marosok,where the hands of merchants and buyer greet each other, there their fingersmutually marosok or fingered ech other. The trader sets the price, and if notmatch the buyer can bid. And keep in mind that when bargaiining takes place thehands of merchants and buyers of cattle are hidden behind sarong, hat or smalltower. The purpouse of this study is to know (1)how the procession of marosoktradition in the sale and purchase transaction of cattle, (2)what is the purpouse ofthe implementation of marosok tradition, and (3)the meaning of each symbol ofthe fingers symbols used in marosok tradition. This research was conducted in themarket of livestock Payakumbuh with descriptive qualitatif research method,where the subject of the study was selected by purposive sampling and snowballsampling. Informants in this study amounted to ten people, who are considered tounderstand very well about this tradition. From the results of interviews andobservations in the field authors concluded that the procession of this tradition isdone by livestock traders, livestock buyers, as well as brokers or intermediaries.The goal of Marosok‟s own tradition is (1)to maintain the tradition it self, (2)toappreciate fellow traders and (3)to the attraction of tourism. And for the symbolof the fingers symbol in bargaining, each finger represents the nominal price, forexample the index finger represents Rp. 100.000 – Rp.10.000.000.Keyword: tradition, marosok, buying and selling